Targeted Anticancer Immunotoxins and Cytotoxic Agents with Direct Killing Moieties - Koji Kawakami; Oumi Nakajima; Ryuichi Morishita; Ryozo Nagai (The Scientific World Journal)
Despite the progress of the bioinformatics approach to characterize cell-surface antigens and receptors on tumor cells, it remains difficult to generate novel cancer vaccines or neutralizing monoclonal antibody therapeutics. Among targeted cancer therapeutics, biologicals with targetable antibodies or ligands conjugated or fused to toxins or chemicals for direct cell-killing ability have been developed over the last 2 decades. These conjugated or fused chimeric proteins are termed immunotoxins or cytotoxic agents. Two agents, DAB389IL-2 (ONTAKTM) targeting the interleukin-2 receptor and CD33-calicheamicin (Mylotarg®), have been approved by the FDA for cutaneous T-cell lymphoma (CTCL) and relapsed acute myeloid leukemia (AML), respectively. Such targetable agents, including RFB4(dsFv)-PE38 (BL22), IL13-PE38QQR, and Tf-CRM107, are being tested in clinical trials. Several agents using unique technology such as a cleavable adapter or immunoliposomes with antibodies are also in the preclinical stage. This review summarizes the generation, mechanism, and development of these agents. In addition, possible future directions of this therapeutic approach are discussed.